Members of the party of right and the idea of the Croat state during the First World War - Matković, Stjepan, povjesničar (Array, 2008)
Summary: The Party of Right, through its various activities, defined Croatian political history from the Party's beginnings in the 1860s to the end of the First World War; after 1918, a newly emergent geopolitical arena brought about by the demise of Austria-Hungary, the collapse of the Habsburg dynasty, and the predominance of Stjepan Radić's peasant ideology on the Croatian political scene relegated Starčević's 'Rightism' to a second rank, rendering it unable to play a leading role in the mass mobilization of members of the Croat national community within the new Yugoslavian monarchy. However, in the late 19th century, adhering to the idea of nationhood proposed by the two founders of the Party of Right, Ante Starčević and Eugen Kvaternik, many modernists in Croatia held to the notion that it was vital to achieve greater independence on the basis of historical Croatian statehood. Considering the popularity of the ideas it proposed, the speed with which they spread, and the influence they had on various social classes, it is indisputable that the Party of Right was the most popular party among Croats during the second half of the 19th century. This is corroborated by the fact that the popularity of 'Rightism' gradually spread beyond the territory of Croatia-Slavonia to Dalmatia, Bosnia and Hercegovina, Istria, and even abroad